Improve the efficiency of the control systems for DC electric elevators using Artificial Intelligence - موسي هازار; مخائيل سليم مخول; ضحى خالد جديد (Latakia University Journal -Engineering Sciences Series, 2023)
The stability of the control system and its high efficiency in various operating conditions is the biggest concern for designers of control systems, this research provides an improved design of a control system used to drive and and control the operation of an electric elevator with a DC motor, a system using (Propotional Integral controller,PI) was developed, the system was also updated from two aspects, the first of which is the introduction of the differential control system, in addition to the use of the Fuzzy control as a debugger supervisory system to the output of the PID system( Propotional Integral Derivative controller), motor speed has been compared with the change of time during start and stop, and the displacement from the stopping point of the elevator, the simulation results using MATLAB/Simulink showed the superiotity of the proposed Fuzzy-Pid system by up to 85.7%,The system has also been tested for different loads, and the results showed an improvement in the shape of the signal when the mass increased with an error rate of 17.2%.